PENGARUH RELIGIUSITAS TERHADAP MOTIVASI KERJA BAGI PEMILIK UMKM (Studi Kasus UMKM Kuliner Bunderan Pasar Jimbaran, Tulangan, Sidoarjo) - Farichatun Ulfah; Ani Faujiah (ICO EDUSHA, 2022)
Covid-19 is a virus that emerged in Indonesia in early 2020. During the emergence of the pandemic, the government implemented several policies, one of which was PPKM. This makes UMKM’s unabele to run their bussines as before. So some UMKM’s choose to close their outlet’s because it has a significant impact. On the other hand, several new UMKM’s appeared due to several reasons, one of which was due to the impact of termination of employment by the previous workplace. Even though the pandemic does not know when it will end, UMKM’s must continue to run their business. Work motivation for UMKM’s is very influential to run their respective businesses to be more optimal. In realizing work motivation, there are psychological factors that can support a person's work motivation, one of which can be realized through religious factors or religiosity. This study aims to find out whether religiosity affects work motivation for UMKM owners in Bunderan Pasar Jimbaran during the pandemic. This research was conducted using a quantitative approach. The number of samples used in this study was 43 respondents. The results showed that the religiosity variable has a significant influence on the variable of a person's work motivation. Based on the results of the religiosity t test, it has a calculated value of 3,365 > 2,021 so that H0 is rejected H1 is accepted. Based on the results of the F test, Fcounts 11,321 > Fof the table 4,085 so that H0 is rejected H1 is accepted. The work motivation according to MSMEs is a spirit and active in work and worship, and has responsibility in a job. It is hoped that the results of this study can be useful in the morning of the author and readers. Keywords: Religiosity, Work Motivation, UMKM, Pandemic References Abdurrahman Firdaus Thaha, “Dampak Covid-19 Terhadap UMKM Di Indonesia,” Jurnal Lentera Bisnis Vol 2 no 1 (2020). Agus Purwanto, “Studi Eksploratif Dampak Pandemi COVID-19 Terhadap Proses Pembelajaran Online Di Sekolah Dasar,” EduPsyCouns: Journal of Education, Psychology and Counseling, Vol. 2, no. 1 (2020). Agus Suprayetno Ida Ayu Brahmasari, “Pengaruh Motivasi Kerja, Kepemimpinan Dan Budaya Organisasi Terhadap Kepuasan Kerja Karyawan Serta Dampaknya Pada Kinerja Persahaan (Studi Kasus Pada PT Pei Hai Internasional,” Jurnal Manajemen dan Kewirausahaan Vol 10, no. 2 (2018). Ananto Pramandhika, “Motivasi Kerja Dalam Islam (Studi Kasus Pada Guru TPQ Di Kecamatan Semarang Selatan),” (Universitas Diponegoro), Skripsi, 2011, hlm. 33 BPS Kabupaten Sidoarjo, “Pertumbuhan Ekonomi Kabupaten Sidoarjo 2020”, Badan Pusat Statistik Kabupaten Sidoarjo (bps.go.id). diakses 7 Desember 2021. Dena Aprilia Anggraeni and Edy Rahardja, “Pengaruh Gaya Kepemimpinan Feminin, Motivasi Kerja Dan Komitmen Organisasional Terhadap Kinerja Karyawan Pt Leo Agung Raya, Semarang,” Diponegoro Journal of Management Vol. 7, no. 4 (2018). Eva Nuroniah and Abdi Triyanto, “Analisis Pengaruh Tingkat Religiusitas Terhadap Kinerja Karyawan Bank Syariah (Studi Kasus Pada Karyawan Kantor Pusat Bank Syariah X),” Jurnal Ekonomi dan Perbankan Syariah Vol. 3 no. 1 (2015). Heru Sulistyo, “Peran Nilai-Nilai Religiusitas Terhadap Kinerja Karyawan Dalam Organisasi,” Media Riset Bisnis & Manajemen, Vol 11, no. 3 (2011). kemenkes RI, “Satgas Covid-19”, https://www.kemkes.go.id/. diakses 7 Desember 2021 Kemenkeu, Pemerintah Terus Perkuat UMKM Melalui Berbagai Bentuk Bantuan, https://www.kemenkeu.go.id. diakses 1 juli 2022 Moh Muslim, "PHK Pada Masa Pandemi Covid-19" 358,” ESENSI: Jurnal Manajemen Bisnis, Vol. 23, no. 3 (2020). Muhammad Nabil Khasbulloh, “Implementasi Kompensasi dan Benefit: Tinjauan Mnjemen SDI Berbasis Syariah,” al-Uqud : Journal of Islamic Economics Vol 2, no. 1 (2018). Noer Soetjipto, "Ketahanan UMKM Jawa Timur Melintasi Pandemi COVID-19", (Yogyakarta: K-Media, 2020), hlm. 23. P. Omollo, Effect of Motivation on Employee Performance of Commercial Banks in Kenya : A Case Study of Kenya Commercial Bank in Migori County., International Journal of Human Resource Studies, Vol. 5, no 2, (2015). Qur’an kemenag, “Q.s Ar-Ra’d Ayat 11,” last modified 2021, https://quran.kemenag.go.id/. diakses Desember 2021. diakses 25 Desember 2021. Qur’an kemenag, “Qs. At-Tin,” last modified 2021, https://quran.kemenag.go.id/sura/95, di akses 7 Desember 2021.